2010
DOI: 10.1590/s0034-89102010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Household members and health care workers as supervisors of tuberculosis treatment

Abstract: OBJECTIVE: To compare tuberculosis cure rates among patients supervised by household members or health care workers. METHODS: Prospective cohort study of 171 patients treated by the program in Vitoria, Southeastern Brazil, from 2004 to 2007. Each patient was followed-up for six months until the end of the treatment. Of the patients studied, a household member supervised 59 patients and healthcare workers supervised 112 patients. Patients' sociodemographic and clinic data were analyzed. Differences between grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…The treatment success rate was 85% and 89% in community and family member based DOTS, respectively. Other studies in Malawi, Thailand, Senegal and South-Eastern Brazil have also shown that family members as supervisors can play an efficient role in DOT in the community (12–15). …”
Section: Discussionmentioning
confidence: 97%
“…The treatment success rate was 85% and 89% in community and family member based DOTS, respectively. Other studies in Malawi, Thailand, Senegal and South-Eastern Brazil have also shown that family members as supervisors can play an efficient role in DOT in the community (12–15). …”
Section: Discussionmentioning
confidence: 97%
“…patients live, their living conditions and family and personal relationships, is essential for monitoring and completion of treatment (7) , for both drug supervision and knowledge of the social context and vulnerability to which patients are exposed, given the importance of this action against a disease that is still a social problem and priority among the goals set by the Millennium Development Goals.…”
Section: Discussionmentioning
confidence: 99%
“…TB poses as an important chronic condition that requires time and commitment from authorities and health professionals (5) , such as the nursing staff. It is the responsibility of these professionals to: search for respiratory symptoms for the early detection of cases, advise on the disease, supervise and guide the medication process, as well as to answer questions and identify potential contacts for the patient among family and the community (6,7) . Eliminating barriers related to the flow of information within and between services and health professionals is key to the integration of activities and services (8) , as this is a significant advance to the measures that must be enhanced to improve assistance to the carriers of TB, such as registration, monitoring and surveillance, as outlined in the World Health Organization (WHO) (1) .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that some Tb patients' low social condition is that obvious that, if no solutions are sought for its improvement, patients are not able to Coping with health needs was qualified as "troublefree" and gratifying but, in most testimonies, it was reported as "very difficulty". Difficulties start before Tb is diagnoses, when the respiratory symptoms have to undergo tests, but refuse to subject themselves to Tb control (8)(9) . When they found out about their Tb diagnosis, most people reacted with fear, refusal and insecurity, and many believe that Tb is an incurable disease (10) .…”
Section: Meanings Attributed To Tuberculosis and Health Needsmentioning
confidence: 99%